Clinical Phenotyping of Long COVID Patients Evaluated in a Specialized Neuro‐COVID Clinic - Luana D. Yamashita; Neel Desai; Abigail R. Manning; Caitlin Pileggi; Sara Manning Peskin; Danielle K. Sandsmark; Dennis L. Kolson; Matthew K. Schindler (Annals of Clinical and Translational Neurology)
ABSTRACT Objective To report Long COVID characteristics and longitudinal courses of patients evaluated between 4/14/21–4/14/22 at the University of Pennsylvania Neurological COVID Clinic (PNCC), including clinical symptoms, neurological examination findings, and neurocognitive screening tests from a standardized PNCC neurological evaluation approach. Methods This is a retrospective cross‐sectional and longitudinal study in a single‐center tertiary care academic center. Participants include 240 patients with documented evidence of a positive SARS‐CoV‐2 PCR or antibody test who underwent initial evaluation and 182 patients with longitudinal follow‐up. Main outcomes evaluated are patient demographics, duration of illness prior to self‐reported improvement, and cognitive testing results—including the Montreal Cognitive Assessment (version 8.2) (MoCA) and Oral Trail Making Test‐B (OTMT‐B). Results The majority (73%) of patients did not require hospitalization for their acute COVID‐19 symptoms. Frequent Long COVID complaints included headache (60%), dizziness/vertigo (40%), and disturbance of taste/smell (40%). Almost all (94%) patients reported cognitive symptoms, and over 30% of patients had abnormal scores on cognitive testing. Severe infection, fewer years of education level, and non‐White race were found to be statistically associated with an increased likelihood of having abnormal scores on cognitive testing. Neuroimaging and clinical laboratory testing were largely not informative for patient care. Sixty‐two percent of patients with follow‐up visits self‐reported improvement in their primary neurological complaint within 1 year of evaluation. Interpretation Performance on standardized cognitive screening tests may not be consistent with frequently reported cognitive complaints in Long COVID patients. The most common clinical trajectory was self‐reported improvement in the primary neurological symptom.